Kinetic and Optimization Study of Green Extraction of Bioactives from Anredera Cordifolia Leaves - Latumakulita, Gertreda; Lodowik Landi Pote; Anggelinus Nadut; Juliano M.P. Umbu Jima Kadebu; Amandha V.D. Tukan (LP2M INSURI Ponorogo, 2025)
The sustainable extraction of bioactive compounds from medicinal plants supports environmentally responsible practices in the pharmaceutical and nutraceutical industries. This study investigates the extraction behavior of Anredera cordifolia leaves using green solvents, with a focus on process optimization and kinetic modeling. A factorial design was used to evaluate the effects of temperature (25–60°C), solvent type (ethanol, methanol, water), pH (4, 7, 9), and time (10–90 minutes). Total phenolic content (TPC) and antioxidant activity were measured via spectrophotometry. Kinetic analysis revealed that the pseudo-second-order model provided the best fit to the data (R² > 0.98), indicating chemisorption as the dominant mechanism. Response Surface Methodology (RSM) identified optimal conditions at 59°C, 70% ethanol, pH 7, and 65 minutes, yielding 213.2 mg GAE/g DW TPC and 91.8% antioxidant activity. Compared to conventional methods, this approach improved yield by 21% and reduced solvent use by 30%. These results demonstrate the value of combining kinetic modeling with statistical optimization to create efficient, scalable, and low-impact extraction protocols. Importantly, the findings offer practical relevance for advancing Indonesia’s herbal industry and supporting the development of sustainable biotechnology in tropical regions.